Online grocery shopping application - Agila, Sivan (2019)
This project is a web based and mobile friendly online grocery shopping application for AKPS Cash & Carry. The aim of this project is to deliver an online grocery application which is allow the customers to buy the groceries online which is simple, fast and cost effective via their smartphones or laptops. Currently, AKPS Cash and Carry staffs find difficulties in handling more customer at a time and the AKPS Cash & Carry owner also want to upgrade the current business technique which is manual sales system. So that, for AKPS Cash & Carry to expand the business of the shop and bring the grocery sales to be online. By making the sales system online, customers can visit AKPS Cash & Carry websites at any time of day or night. Online Shopping are usually available 24 hours a day and many customers have internet access both at work and at home. So, it is very convenient for them to purchase households online. Moreover, this application allows the customers to make their purchase payment through online payment through PayPal payment gateway over the internet. Besides that, this application allows the staffs to manage the products and to generate business related reports of the AKPS Cash & Carry and it helps to keep track the sales information’s. This application is develop using Waterfall methodology as it is designed to provide faster development and high-quality results. In conclusion, online shopping is one of the greatest aspects of the internet today. By choosing to shop online customer will be able to get many benefits for customers, it helps customer to save their time, their money and goods in online shop are so variety and its very convenient for people.